Tilshunoslikda anakoluf tushunchasi haqida - Jo'rayeva Nodira Abdujamil qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In recent years, great attention is paid to stylistic issues in our country and abroad. But stylistics as a separate branch of linguistics is still underdeveloped. If we turn to the stylistics of modern Chinese, there are many gaps, as well as unexplored aspects. One such unexplored phenomenon is anakoluf. Anakoluf are phrases with a semantic content that change the syntactic structure and intended meaning of a sentence after a break. In a broad sense, the anacoluf is used as a rhetorical figure in order to encourage students and listeners to think deeply.